Linear displacement measuring system based on electromagnetic phase shifter - O.K. Abdirashev (Известия высших учебных заведений. Поволжский регион:Технические науки, 2021)
Background. The principle of automated control and monitoring systems’ operation is based on the widespread use of devices for measuring angular and linear displacement At the same time, the main requirement for these devices is high reliability, safety and properties of the output signal, convenient for further use. As a rule, the output signal of devices for measuring the parameters of linear and angular displacements should be in digital form at the present level of development. At the same time, the urgent task is to ensure high accuracy of movements in the measuring transducers and the conversion of the initial value into an electrical signal. Electrical form of the output signal of the primary measuring transducer is most convenient for further processing and use in subsequent stages of robotic systems and complexes. The purpose of the work is to develop measuring transducers based on electromagnetic phase shifters of angular displacements based on a non-uniform magnetic circuit with distributed parameters. Materials and methods. Research of the processes occurring during the operation of an electromagnetic converter with a non-uniform magnetic circuit with distributed parameters, which implements the functions of a linear phase shifter. Results. A methodology and mathematical model have been developed. The technique allows you to calculate the absolute error from the influence of any factor. The resulting variance from the action of all factors will depend not only on the variance of each factor, but will be the result of the interaction of these factors. With the help of a mathematical model, studies of the developed measuring system were carried out in order to obtain a decomposition of the absolute errors of the system into components along the axes of a multidimensional space. Conclusions. The obtained research results consist in the use of the methodology for the design of measuring systems of linear displacements to obtain tolerances for the manufacture of individual elements of the electromagnetic system and the formation of requirements for the characteristics of the measuring system blocks based on the obtained mathematical model.